A Top Down Strategy to Enhance Information Technologies into Israeli Higher Education - Guri-Rosenblit, Sara (International Review of Research in Open and Distributed Learning, 2002)
This article examines the integration of the new information technologies (IT) into Israeli higher education, and most particularly its research universities through a top-down strategy, initiated by the Israeli Council for Higher Education since the end of 1999. This top-down strategy has created a systemic change that will affect the many layers of university activities rather than in a random, sporadic manner undertaken by enthusiastic individuals. This article discusses the built-in contradictions and dilemmas in the process of adapting distance teaching methods by conventional universities in Israel (as well as in other higher education systems). It examines the merits of a top-down strategy aimed to implement the IT through a macro-level, systemic approach, and analyses the differential uses of the IT in Israeli higher education institutions, relating to variables of: access-outreach; teaching-learning processes; study materials production; data and information retrieval; administrative functions; the creation of "researcher" communities; inter-institutional collaboration; and associated costs. The article concludes with some suggestions for effective implementation of the IT in different types of higher education institutions in a comprehensive and systematic manner, that will take into account their academic ethos and organizational infrastructure, and cater to the unique needs and characteristics of their relevant constituencies.